TRANSLATION ANALYSIS OF RESTAURANT MENUS - Sumardiono Sumardiono; Ch. Evy Triwidyahening (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2023)
This qualitative and descriptive research investigates the translation techniques utilized for restaurant food menus into English and the subsequent impact on translation quality, including accuracy, acceptability, and readability. This qualitative and descriptive research investigates the translation techniques utilized for restaurant food menus into English and the subsequent impact on translation quality, including accuracy, acceptability, and readability. The research data comprises the menu item names and their corresponding English translations, gathered from documents. Precisely explaining technical term abbreviations has been prioritized in the research. The data collection technique involves document analysis. It was discovered through this analysis that the description technique constitutes 66% of the total techniques used, with common equivalence at 23% and pure borrowing + common equivalence at 4.8%. The least frequent techniques were pure borrowing, variation borrowing, and explicitness + conventional equivalence, all at 0.9%. In general, the quality of translation for the restaurant's food menu is very good, with an average rating of 2.93, which is above the average for translation quality. Keywords: food menu translation, translation techniques, translation quality.